Strengthening Sciencitic Literacy Through STEM Learning in Elementary Schools: Community Service Efforts in Rural Areas - Sanju Aprilisia; Santosa, Tomi Apra; Mohammad Edy Nurtamam; Sukini, Sukini; Ilwandri, Ilwandri; Wulandari, Andi Sri Rezky; Elismayanti Rembe; Insira Insani Fitri (Journal Of Human And Education (JAHE), 2024)
Strong science literacy skills are an important foundation for the younger generation. This study aims to examine how STEM (Science, Technology, Engineering, Mathematics) learning can be used to improve science literacy in elementary school students, especially in rural areas. This research uses a community service approach. This community service activity involves the implementation of STEM learning programs designed specifically for elementary school students in rural areas. This program integrates science, technology, engineering, and mathematics-based learning activities. The result of this study is STEM learning in improving the science literacy of elementary school students in rural areas. The findings of this study can contribute to the development of more innovative and effective learning practices to improve students' science literacy, especially in rural areas. This research is also expected to encourage synergy between academics and the community in an effort to improve the quality of science education in rural areas.